Reflections on conducting research in uncertain times. Issue 3 (4th May 2022) - Shinew, Kimberly; Gibson, Heather; Schneider, Ingrid; Wynveen, Chirstopher; Hendricks, William; Budruk, Megha; Farrell, Eve
ABSTRACT: A group of researchers came together during the COVID-19 pandemic to conduct an observational study on trail use behaviour. The purpose of this paper is not to report on the trail data collected, but to reflect on the research process during an unprecedented time. Specifically, the objectives of the paper are to identify challenges and tensions of collecting data during a pandemic, and reflect on the unanticipated rewards that arose while conducting such research. The paper relies on vignettes/reflections from seven researchers who shared stories that exemplified their data collection experiences during the first three months of the project. The researchers' reflections provide an insider view into the challenges they faced. Using thematic analysis, themes about logistical difficulties, safety concerns, sense of time, and making connections were identified. The challenges and the importance of the researchers' relationships with one another were evident in the reflections. In sharing their reflections, the hope is that their experiences may inform future fieldwork during difficult periods. This study examined some of the challenges of collecting data during a pandemic and the tensions that occurred, but there are lessons here for other stressful and unique research situations.